Shear behaviour and mechanical properties of steel fibre-reinforced cement-based and geopolymer oil palm shell lightweight aggregate concrete. (1st September 2017) - Mo, Kim Hung; Yeoh, Khai Hung; Bashar, Iftekhair Ibnul; Alengaram, U. Johnson; Jumaat, Mohd Zamin
Highlights: Shear behaviour of steel fibre cement-based and geopolymer OPS LWAC investigated. Mechanical properties comparison of steel fibre cement-based and geopolymer LWAC. Tensile strength and toughness increase more evident for cement than geopolymer LWAC. Shear capacity improved with fibres and existing prediction equations are conservative. Abstract: The shear behaviour and mechanical properties (compressive, splitting tensile and flexural strengths) as well as the flexural toughness of steel fibre-reinforced cement-based and geopolymer oil palm shell lightweight aggregate concrete (OPS LWAC) were experimentally investigated in this paper. Steel fibres were added at various volume fractions for the cement-based OPS LWAC (0%, 0.5% and 1.0%) and geopolymer OPS LWAC (0%, 0.5%). Test results showed that steel fibre improved the mechanical properties of concrete, particularly for the splitting tensile strength whereas flexural toughness enhancement with the use of steel fibres was more evident for the cement-based OPS LWAC than the geopolymer concrete. The shear resistance of OPS LWAC beams was also found to improve with the addition of steel fibres and existing prediction equations for shear capacity of steel fibre-reinforced lightweight concrete was determined to be conservative for the steel fibre-reinforced cement-based and geopolymer OPS LWAC.